Study of the accuracy characteristics of a GNSS receiver with an antenna array - V. N. Tyapkin; A. B. Gladyshev; D. D. Dmitriev (Космические аппараты и технологии, 2023)
The article presents the results of experimental studies of the accuracy of measuring navigation parameters by a receiver of global navigation satellite systems (GNSS receiver) equipped with an antenna array. The use of ring antenna arrays in GNSS receivers is substantiated. The main advantage of such antenna arrays is their invariance to the direction of the main lobe of the radiation pattern in the azimuthal plane. However, ring antenna arrays have some disadvantages. The use of the minimum required number of radiators in such antenna arrays to form a beam of a given width leads to a simultaneous increase in the level of side lobes. However, when using ring antenna arrays in GNSS receivers, this drawback can be neglected, since the level of side lobes significantly affects the quality of navigation signal reception only with powerful signal re- reflections. The structure of the hardware- software complex for research is given and the principle of its operation is described. Its main parts are a 24-channel beam- forming GNSS receiver and an 8-element ring antenna array. The software and hardware complex allows the study of various configurations of antenna arrays – two, four and eight elements. The technique of carrying out the experiment is given. A eature of the technique is the use of differences in measured pseudoranges using a single antenna and various configurations of antenna arrays. The results of measurements of code and phase pseudorange are presented.